2016
DOI: 10.5430/ijhe.v5n3p20
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mobile Learning on Students' Achievement and Conversational Skills

Abstract: The present study aimed to examine the effect of Mobile Learning, which is a kind of E-learning that uses mobile devices, on the development of the academic achievement and conversational skills of English language specialty students at Najran University. The study used the quasi-experimental approach. Participants consisted of (50) students who were registered in a course called "Strategies of Teaching and Learning" offered by the Department of Curriculum and Instruction at the College of Education to student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 18 publications
9
53
0
4
Order By: Relevance
“…Based on the data analysis for the first hypothesis testing, it reveals that the group with android-based learning media achieves higher mean score compared to the group that used powerpoint-based learning media. So there is an influence of learning models toward student learning outcomes, where android-based learning media is more effective than the powerpoint-based learning media in improving student learning outcome of Indonesian Economics subject These results are in line with the research conducted by Elfeky & Masadeh [7] that shows mobile learning can improve the learning outcomes because trough mobile learning learners can access lessons and assignments anywhere and anytime. While for teacher, mobile learning can help to upload teaching materials, determine the discussion and accept the students' tasks electronically.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Based on the data analysis for the first hypothesis testing, it reveals that the group with android-based learning media achieves higher mean score compared to the group that used powerpoint-based learning media. So there is an influence of learning models toward student learning outcomes, where android-based learning media is more effective than the powerpoint-based learning media in improving student learning outcome of Indonesian Economics subject These results are in line with the research conducted by Elfeky & Masadeh [7] that shows mobile learning can improve the learning outcomes because trough mobile learning learners can access lessons and assignments anywhere and anytime. While for teacher, mobile learning can help to upload teaching materials, determine the discussion and accept the students' tasks electronically.…”
Section: Discussionsupporting
confidence: 80%
“…According to Huang, Jeng & Huang [6] mobile learning has features in the form of availability and accessibility of information networks, enable to involve learn-ers in learning related to the different environmental circumstances, can help group works, increase the communication and cooperation in learning in the classroom and can deliver learning quickly. Based on the result of research by Elfeky & Masadeh [7] mobile learning can improve learning outcomes because mobile learning enables learners to access lessons and assignments anywhere and anytime. While for teacher, mobile learning can help to upload teaching materials, determine the discussion and accept the students' tasks electronically.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile learning is more effective than the use of traditional teaching methods in helping students enrolled in the "Strategies of Teaching and Learning" course to achieve better and develop their skills (Elfeky & Masadeh, 2016). These features are provided in a very supportive Android learning because it is beneficial to help students to understand the subject matter.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified advantages of mobile devices including their portability, versatility of features, connectivity, and individuality [6,11,12]. Their portability, combined with the pervasive presence of mobile devices in daily life, enables learners to use handheld devices anytime they want [9,[13][14][15]. In addition, research on language learning can be conducted not only in formal classrooms but also in informal settings such as during language use at home and in social communication.…”
Section: Introductionmentioning
confidence: 99%